ANALISIS KETERKAITAN ANTARA DANA CADANGAN DAN ASET PUBLIK TERHADAP GOOD GOVERNANCE - Aminatuzzuria, Maritza; rahmawati, Sheila; Anam, Rohibul; Djasuli, Mohamad (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: Good governance is a key principle in state financial management that aims to achieve transparency, accountability, efficiency and public participation. In this context, reserve funds and public assets are important instruments that can strengthen governance. This study aims to analyze the relationship between the management of reserve funds and public assets and the implementation of good governance principles, especially in maintaining fiscal stability and supporting sustainable development. Methods: This research is a literature review based on academic journals, policy papers, and official government documents. A qualitative, descriptive-analytical approach was applied to identify the linkages between reserve funds, public assets, and good governance. Results: The study finds that transparent and accountable management of reserve funds boosts public trust and strengthens fiscal resilience. Likewise, optimizing public assets improves resource efficiency and contributes to inclusive economic growth. Both elements significantly support governance, particularly in enhancing transparency, accountability, and fiscal efficiency. Conclusion and suggestion: This study emphasizes the importance of integrating good governance principles in the management of reserve funds and public assets. Good management of these two components can strengthen fiscal stability, improve the efficient use of state resources, and build public trust in government institutions. Therefore, it is recommended that policymakers formulate a more transparent, accountable and participatory public financial management strategy. This study provides a new perspective on the synergy between state financial instruments and good governance in supporting sustainable development. Keywords: Reserve funds, Public assets, Good governance.